Analyzing The Impact of Financial Literacy on Investment Interest with Locus of Control as The Mediating Variable - Aulia Falyauma Risky; Mychelia Champaca (Jurnal Management Risiko dan Keuangan, 2025)
Indonesian investment and financial markets, which were then considered exclusive and complicated, are now growing rapidly. University students’ role in the capital market reflects a better financial behavior, and this is supported by their sufficient financial literacy that makes way for more comprehensive financial inclusion. All of these lead to a notion that financial behavior, financial literacy, and locus of control play a crucial role in increasing individuals’ investment intention. Therefore, the objective of this research is to identify and analyze the effects of financial behavior and financial literacy on the intention of graduate students of Faculty of Economics and Business of Universitas Brawijaya to make investments with locus of control as the moderating variable. This replication study uses primary data harvested via a survey technique to respondents selected using purposive sampling technique. The acquired data was analyzed through multiple linear regression. This study finds that financial behavior and financial literacy influence the investment intention and that locus of control does not moderate the effects of financial literacy on the investment intention.